DAMPAK PELANGGARAN KODE ETIK FIRLI BAHURI TERHADAP KINERJA DAN CITRA KOMISI PEMBERANTASAN KORUPSI (KPK) - Darussalam , Mohammad; Budhiartie2, Arrie (STIS Darussalam Bermi, 2024)
The abstract contains the objectives of analyzing the ethical violations committed by Firli Bahuri, the Chairman of the Corruption Eradication Commission (KPK), and their impact on the institution's performance and image. Through a qualitative descriptive method, this study examines media reports, expert opinions, and legal documents to interpret and synthesize the findings. Results indicate that ethical violations by the KPK leader weakened public trust, disrupted institutional performance, and prompted calls for internal reform. It is concluded that stronger ethical enforcement and public accountability are crucial to restoring the integrity of anti-corruption bodies.